Performance evaluation of hydraulic ram pumping systems for small-scale farmers: a case study of West Pokot county, Kenya. Issue 1 (15th December 2022) - Osome, Joseph Kisia; Kosgei, Job Rotich; Kipkorir, Emmanuel Chessum; Nyandwaro, Gilbert Nyageikaro; Sempewo, Jotham Ivan
Abstract: Hydraulic ram (hydram) pump has been in existence for more than two centuries. However, these pumps have been on the verge of extinction since the invention of motorized pumps, which are more powerful and efficient. Unfortunately, motorized pumps are expensive to acquire, operate, and maintain. Their contribution to climate change and environmental degradation has steered the need for an alternative pumping technology. Therefore, as the world's technology shifts to green energy, hydram pumps need to be re-invented. In the late twentieth century, studies on hydram pumps have been revived with the aim of making them more efficient and economically competitive. Small-scale farmers in West Pokot County, Kenya, have embraced the hydram technology, but due to low technical capacity; installed low-performing hydram that operated under low efficiencies of less than 30%, with the majority having operational failure due to inadequate designs. Hence, this study investigated the design and operation of these pumps. Thereafter, designed and assembled a hydram pump, using locally available materials, to supply water for domestic and small-scale agricultural use. The optimum efficiency achieved by the pump was 54%, with an optimum delivery flow rate of about 13 L/min. HIGHLIGHTS: The locally installed hydraulic ram pumping system performs way below its potential due to low technical know-how. The study assesses the performance, thereafter, designs a prototype pump that can cheaply be fabricated by local farmers for irrigation. The fabricated pump exhibits higher efficiency compared to the existing hydraulic ram pumping systems. The study aims to make the pump economically competitive. Graphical Abstract